Magersfontein, o Magersfontein! as 'n wending tot die realisme in die werk van Etienne Leroux (Afrikaans) - Roodt, P.H. (Pieter Hendrik) (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2013.